+0  
 
0
38
2
avatar+120 

Solve the Equation

14-3(x+9)=5

ManuelBautista2019  Nov 6, 2017
Sort: 

2+0 Answers

 #1
avatar+78756 
+4

14 - 3(x+9) = 5     distribute the 3 across the terms in the parentheses

 

14 - 3x - 27   =  5       

 

14 - 27  - 3x  =  5

 

-13   - 3x  =   5  add 13 to both sides

 

-3x  =  18       divide both sides by -3

 

x  =   -6

 

 

cool cool cool

CPhill  Nov 6, 2017
 #2
avatar+499 
+1

14-3(x+9)=5

 

Subtract 14 from both sides.

 

14-3(x+9)-14=5-14

 

Simplify

 

-3(x+9)=-9

 

Divide both sides by -3

 

 

Simplify

 

x+9-9=3-9

 

Subtract 9 from both sides

 

x+9-9=3-9

 

Simplify

 

x=-6

 

laughlaughlaugh

ProMagma  Nov 6, 2017

7 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details